2003
DOI: 10.1007/s00253-003-1404-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching review part B:

Abstract: This review describes the historical development and current state of metals leaching and sulfide mineral biooxidation by the minerals industries. During the past 20 years commercial processes employing microorganisms for mineral recovery have progressed from rather uncontrolled copper dump leaching to mineral oxidation and leaching in designed bioheaps for oxidation of refractory gold ores and for copper recovery. Also during this period of time, stirred tank bioleaching has been commercialized for cobalt rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(106 citation statements)
references
References 46 publications
1
80
1
3
Order By: Relevance
“…Peeples and Kelly (28) have shown that M. prunae may oxidize Fe(II) as a sole energy source, and several studies have noted that Metallosphaera spp. are effective in accelerating the dissolution of pyrite and the release of metals in biomining applications (27,30,32).…”
mentioning
confidence: 99%
“…Peeples and Kelly (28) have shown that M. prunae may oxidize Fe(II) as a sole energy source, and several studies have noted that Metallosphaera spp. are effective in accelerating the dissolution of pyrite and the release of metals in biomining applications (27,30,32).…”
mentioning
confidence: 99%
“…[22,23]. [24] Postrojenje i lokacija Veličina (tona koncentrata/dan) Tehnologija Godine rada hidrit/gips-precipitat iz neutralizacije krečnjakom rastvora nakon luženja i bogat mineralni ostatak. Oba ostatka mogu biti modifikovana različitim metal ekstrakcionim procedurama (uglavnom ekstrakcija/elektroliza za bakar, precipitacija karbonata ili hidroksida za nikl i cijanidna/ugljenična adsorpcija zlata) [25].…”
Section: Biološko Luženje Polimetaličnih Ruda Koje Sadrže Zlatounclassified
“…Mixed cultures of A. ferrooxidans and A. thiooxidans and some other acidophiles have been confirmed to be predominant bioleaching bacteria which can effectively oxidize and release metals or metalloids in the leachates during the bioleaching and bio-oxidation of sulfide ores, such as arsenic-bearing refractory gold ore [9,[11][12][13][14]. However, only one strain of A. ferrooxidans and another strain of A. thiooxidans were employed in that report, and comparison of bioleaching behavior between mixed unadapted cultures and adapted cultures was not investigated.…”
Section: Acidithiobacillusmentioning
confidence: 99%
“…ferrooxidans and Acidithiobacillus thiooxidans are two of the most important bioleaching micro-organisms [7][8][9][10]. Mixed cultures of A. ferrooxidans and A. thiooxidans and some other acidophiles have been confirmed to be predominant bioleaching bacteria which can effectively oxidize and release metals or metalloids in the leachates during the bioleaching and bio-oxidation of sulfide ores, such as arsenic-bearing refractory gold ore [9,[11][12][13][14].…”
Section: Acidithiobacillusmentioning
confidence: 99%